Os estudos clássicos no Brasil colonial: uma breve proposta para a reintrodução de um assunto - Beccari, Alessandro Jocelito [UNESP]; Binato, Cláudia Valéria Penavel [UNESP] (My University, 2012)
This paper wishes to reintroduce, in a brief manner, a subject which has been neglected in the recent past: the history of Classical Studies in colonial Brazil. As an introduction to this complex issue, it aims at a historical review of the ideal of humanitas in the Academias of the eighteenth century. The presence of this ideal in the Academias is seen as a result of the classical education of the Brazilian people, a process which begins with the arrival of Jesuit missionaries in 1549 and 1553. In our discussion, we shall use the ideas of Dante Tringali (1994), Fernando de Azevedo (1958), Antônio Cândido (1977), José Aderaldo Castello (1969), among others.

Este artigo quer reintroduzir, de forma sucinta, um assunto hoje pouco estudado no país: a história dos estudos clássicos no Brasil Colonial. Como introdução a esse assunto complexo, pretende-se uma visada histórica do ideal de humanitas nas academias do séc. XVIII. A presença desse ideal nas academias é vista como consequência da formação clássica do povo brasileiro, tendo-se em conta que essa formação começa com a vinda dos jesuítas em 1549 e 1553. Em nossa discussão, faremos uso das ideias de Dante Tringali (1994), Fernando de Azevedo (1958), Antônio Cândido (1977), José Aderaldo Castello (1969), entre outros.
Classical Studies in colonial Brazil: a brief proposal for the reintroduction of a topic
Keywords: Classical Studies; Colonial Brazil; Academias; Humanitas; Estudos Clássicos; Brasil Colonial; Academias; Humanitas